Formation and Variation of the Atmospheric Heat Source over the Tibetan Plateau and Its Climate Effects - Wu, Guoxiong; He, Bian; Duan, Anmin; Liu, Yimin; Yu, Wei (Advances in atmospheric sciences, 2017)
To cherish the memory of the late Professor Duzheng YE on what would have been his 100 th birthday, and to celebrate his great accomplishment in opening a new era of Tibetan Plateau（TP） meteorology, this review paper provides an assessment of the atmospheric heat source（AHS） over the TP from different data resources, including observations from local meteorological stations, satellite remote sensing data, and various reanalysis datasets. The uncertainty and applicability of these heat source data are evaluated. Analysis regarding the formation of the AHS over the TP demonstrates that it is not only the cause of the atmospheric circulation, but is also a result of that circulation. Based on numerical experiments, the review further demonstrates that land–sea thermal contrast is only one part of the monsoon story. The thermal forcing of the Tibetan–Iranian Plateau plays a significant role in generating the Asian summer monsoon（ASM）, i.e., in addition to pumping water vapor from sea to land and from the lower to the upper troposphere, it also generates a subtropical monsoon–type meridional circulation subject to the angular momentum conservation, providing an ascending-air large-scale background for the development of the ASM.